Prolonged lockdown: psychological risk factors among children and their mental health - Ilyas, Uzma; Farooqi, Rabia (Journal of the Pakistan Medical Association, 2021)
The most talked phenomenon and sui generis of the modern time, the coronavirus diseases-2019 impacted individuals in a variety of ways. Older adults had a higher risk of vulnerability, while there were negative ramifications among children due to indirect impact. The preventive measures, including closing down of schools, malls and playgrounds as well as practising social distancing served as a shield against the hazard of outbreak. On the contrary, these strategies inculcated fear, anxiety, ambiguous communication and manifestation of externalizing behaviours in children. Children living in dysfunctional families in underprivileged circumstances were more susceptible to abuse during the pandemic, and had increased risk of behavioural symptomology and psychological morbidities. Challenges brought by the new normal for children requires redefining the role of parenting for effective monitoring and intervention to mitigate the symptoms. Preventive strategies outlined by international scientific communities include reflective listening, debriefing and psychological first aid for effective